FREEDOM OF THE MEDIA IN CROATIA IN THE YEAR OF 1989/1990 ILLUSTRATED WITH AN EXAMPLE OF THE CITY OF ZADAR - Marijana Raznjevic Zdrilic (European Scientific Journal, ESJ, 2015)
This paper explores the issue of freedom of the media illustrated with an example of the local press. The paper is based on an analysis of the content of newspaper articles on legislative changes published in local newspapers – a weekly Narodni list and a monthly Fokus, published in the city of Zadar in Croatia in 1989 and 1990, and relating to the topics of media freedom and pluralism. The analysis of the content of newspaper articles included articles published from February 9, 1989 to September 22, 1990, which is the period when the monthly Fokus was published. The period researched was an extremely important and turbulent period for Croatia as it had to constitute its sovereignty as well as independence in the initial transition period. In 1989, Croatia was still a part of the multinational Socialist Federal Republic of Yugoslavia and political disagreements among the republics resulted in the dissolution of Yugoslavia. Croatia gained its independence fighting in the Homeland War from 1991 to 1995, basic preconditions for the development of democratic society thus being put in background. Changes in the field of media occurred along with social and political changes. Media played a key role in the process of democratization in Croatia. The Croatian press was a significant participant of democratic events in Croatia for the period researched, and later. The research was based on an analysis of 104 newspaper issues, comprising a corpus of 1175 newspaper articles, 149 of which belonged to the category of The Freedom of the Media. Descriptive and explanatory methods were employed in the paper, as well as the method of qualitative and quantitative content analysis. The research results have shown the local newspapers actively informed their readers about matters of media freedom and pluralism.